Depression in women with a diagnosis of breast cancer. Prevalence of symptoms of depression in Peruvian women with early breast cancer and related sociodemographic factors - Casavilca-Zambrano, Sandro (2020)
We sought to review literature on the prevalence of symptoms of depression in women with a diagnosis of breast cancer (BC) and in the Peruvian population determine the prevalence of symptoms of depression and to describe the association with sociodemographic characteristics. Descriptive cross-sectional analytical study of 254 patients from the National Cancer Institute of Peru (Instituto Nacional de Enfermedades Neoplasicas) with a diagnosis of clinical stage I or II BC. The patients included women aged between 26 and 67 years old. Symptoms of depression were monitored by the Beck Depression Inventory-II. Moreover, clinical features and patient sociodemographic characteristics were analyzed and their association with depression was assessed by logistic regression. The average age of the patients was 47.8 +/- 9.2 years; 5.4% of the patients were postmenopausal at the time of the questionnaire. About 55% of women were from Lima, 58.3% had completed secondary education (11 +/- 3.2 years), 45.7% were not working, and 46.5% were single. The prevalence of depression was 25.6% at the time of BC diagnosis. Of those patients with symptoms of depression, 16.9% showed symptoms of mild depression, 6.3% moderate, and 2.4% severe. A multivariable logistic regression model showed that in Peruvian women with a diagnosis of BC being married or employed significantly decreased the odds of presenting depressive symptoms (P=0.029 and 0.017, respectively). Our main limitation was the lack of evaluation of depressive symptoms before the diagnosis, during or at the end of treatment. Another limitation was that the Beck Depression Inventory-II test could only identify depressive symptoms, but not depression as a disease. We have reviewed relevant literature on depression in women with a diagnosis of BC. The data presented suggests an association between both employment and marital status with depressive symptoms among Peruvian women with a diagnosis of BC. Pre-emptive support for women at risk could influence resilience and/or motivation for compliance with antineoplastic treatments. (C) 2020 Elsevier Inc. All rights reserved.